Acesso e utilização aos serviços de atenção primária à saúde pela população urbana no município de Jequitinhonha, Minas Gerais - Izabela Rocha Dutra (2009)
It is believed that the evaluation of the access and use of the services of Primary Attention toHealth can generate information that will lead to the invigoration and the operationalefficiency of the services of attention to the health, and the consolidation of the guidelines,and integrality proposed by Health System. This study had the objective to evaluate thefactors related to the access and use of the health services in 1235 individuals of the urbanarea, in the District of Jequitinhonha, Minas Gerais. The collection of data was made throughquestionnaires on demographics, socioeconomic status and with regards to the access andthe use of the services of Primary Attention to Health. We also performed interviews with thehealth professionals and local managers. Our results showed that upon the appearance ofhealth problems, the majority of the individuals seek access the Basic Units of Health. Inother cases, they prefer to access the hospital, use self-medication or to use home-madeteas. In the last 12 months previous to the research, most the individuals accessed thehealth services to consult with health professionals. Among the ones whom awaited theresults of exams and specialized consultations, the waiting time varied among 1 to 3 monthsor more. The presence of symptoms in the last 30 days that preceded the researchhappened in half the participants and some of them had their habitual activities restricted.The use of the health services in this same period was less used by a few of theinterviewees, half being women and older individuals (equal or more than 60 years of age),with less education and retired or unemployed. The reasons that determined that use werethe presence of symptoms or disease, and the control of chronic diseases. The choice toseek the service was motivated by having registered in the health unit, and its proximity topatients home. With the search, in general, the individuals received free service andmedication, they spent about 30 minutes from home until their assistance. A small portion ofthe interviewees was not assisted in the first moment that looked for service, with theabsence of vacancies for the service, the lack of health professional and of medication as themain reasons. In spite of that, the participants evaluated as very good and good the receivedservice although they suggested improvements for the services of health. For the individualsthat didn't use the services of health in the last 30 days preceding the study, the reasonswere the lack of need, self-medication and the use of home-made teas. The results of thisstudy demonstrated that the service of Primary Attention in Health in the district ofJequitinhonha is not a problem for most of the interviewees. However it is necessary todeepen the knowledge on some aspects that involve the system of health in this district,leading to discoveries for the existing organizational obstacles that can hinder the accessand use of the services for the people. Besides, the need to create mechanisms to modifythe profile of use of the units of reference for the primary attention to the health, wasdetected, consolidating them as the main access to the system. Furthermore, the user'sdissatisfaction as for the wait for consultations and specialized exams, harmed the continuityof the attention to the health and indicated the need of more detailed studies than integrateand deepen subjects related to the access and use, as well as the resolute satisfaction andquality of the average services and high complexity.